Phylogeny affects host’s weight, immune response and parasitism in damselflies and dragonflies - Jaakko J. Ilvonen; Jukka Suhonen (The Royal Society Publishing, 2022)
Host-parasite interactions are an intriguing part of ecology, and understanding how hosts are able to withstand parasitic attacks, e.g. by allocating resources to immune defense, is important. Dragonflies and damselflies show a variety of parasitism patterns, but large-scale comparative immune defense studies are rare and it is difficult to say what the interplay is between their immune defense and parasitism. The aim of this study was to find whether there are differences in immune response between different dragonfly and damselfly species and whether these could explain their levels of gregarine and water mite parasitism. Using an artificial pathogen, a piece of nylon filament, we measured the encapsulation response of 22 different dragonfly and damselfly species and found that (i) there are significant encapsulation differences between species, (ii) body mass has a strong association on encapsulation and parasitism levels, (iii) body mass shows a strong phylogenetic signal whereas encapsulation response and gregarine and water mite parasitism show  weak signals and (iv) associations between the traits are affected by phylogeny. We do not know what the relationship is between these four traits, but it seems clear that phylogeny plays a role in determining parasitism levels of damselflies and dragonflies.